Mapping of Basin Substrate and Vulnerability Index of Shallow Waters of Combol and Citlim Island, Moro District, Karimun Regency, Riau Islands Province, Indonesia - Aunurrahman; Hanifa, Irfan; Setiyaningsih (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Mapping basin substrates and vulnerability indexes in shallow waters are crucial for understanding the ecological health and resilience of marine ecosystems. Given the increasing threats from climate change and human activities, this research provides essential insights for effectively managing and conserving these vital coastal environments. Our study discusses mapping the bottom substrate and the vulnerability index of shallow waters in the Combol and Citlim Island clusters, Moro District, Karimun Regency, Riau Islands Province. Shallow waters have rich ecosystems, including coral reefs and seagrass beds, which function as fish habitats and coastal protection. However, these ecosystems are vulnerable to climate change and pollution disturbances. Using the water column correction method, this study used Sentinel-2A multispectral satellite imagery to map the shallow water bottom habitat. The analysis showed that open substrates and dead corals dominated the habitat, with an area of ​​± 766.8 Ha and ± 682.5 Ha, respectively. The vulnerability index revealed that a total area of approximately 393 ha fell into the moderate vulnerability category. Our mapping result is essential for understanding ecosystem dynamics and formulating appropriate conservation strategies. We anticipate that these findings will offer valuable insights for managing aquatic resources and safeguarding coastal ecosystems in the region.